Accounting undergraduate curriculum: a comparison between Brazil, the USA and the UK. (2015) - Murcia, Flávia Cruz de Souza; Murcia, Fernando Dal-Ri; Rover, Suliani; Pfitscher, Elisete Dahmer
Recent criticism suggesting that accountants lack adequate critical and analytical skills, and the adoption of IFRS in 2010 as well as the globalisation of accounting professional, have made many Brazilian universities rethink their accounting undergraduate curriculum. Wishing to make a contribution to this discussion, this paper compares the accounting undergraduate curriculum of Brazilian state universities with the top accounting undergraduate programs in the USA and in the UK. Our findings evidenced that Brazil has a more rigid and technically oriented accounting curriculum, as the great majority of courses are mandatory and in the accounting area. The US model is more flexible, allowing students to take several courses in non-business areas like liberal arts, social sciences and natural sciences. The UK curriculum is a midterm between the Brazilian and US ones, and closer to the first one. It is also very technical, but more finance oriented as there are several courses related to finance and economics.